2012
DOI: 10.1136/bmjopen-2011-000747
|View full text |Cite
|
Sign up to set email alerts
|

Incentivising safe sex: a randomised trial of conditional cash transfers for HIV and sexually transmitted infection prevention in rural Tanzania

Abstract: ObjectiveThe authors evaluated the use of conditional cash transfers as an HIV and sexually transmitted infection prevention strategy to incentivise safe sex.DesignAn unblinded, individually randomised and controlled trial.Setting10 villages within the Kilombero/Ulanga districts of the Ifakara Health and Demographic Surveillance System in rural south-west Tanzania.ParticipantsThe authors enrolled 2399 participants, aged 18–30 years, including adult spouses.InterventionsParticipants were randomly assigned to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
172
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(176 citation statements)
references
References 20 publications
4
172
0
Order By: Relevance
“…Two studies were conducted in sub-Saharan Africa (SSA) [40,41] and one in the USA [42]. In general study design was rigorous, using RCTs in two studies [40,41] and a quasi-experimental design in the other [42]. In Tanzania remaining STI-free was incentivised with cash and assessed through testing every 4 months over a 12-month period [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies were conducted in sub-Saharan Africa (SSA) [40,41] and one in the USA [42]. In general study design was rigorous, using RCTs in two studies [40,41] and a quasi-experimental design in the other [42]. In Tanzania remaining STI-free was incentivised with cash and assessed through testing every 4 months over a 12-month period [40].…”
Section: Resultsmentioning
confidence: 99%
“…In general study design was rigorous, using RCTs in two studies [40,41] and a quasi-experimental design in the other [42]. In Tanzania remaining STI-free was incentivised with cash and assessed through testing every 4 months over a 12-month period [40]. In Malawi a study focused on incentivising maintaining HIV status over 12 months for women and men (if HIV-negative at start, maintaining this; if HIV-positive, they automatically received the cash transfer at the end) [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many programmes, however, target behaviours with corresponding health benefits that require ongoing maintenance. For example, the RESPECT programme in Tanzania incentivised safe sex practice, as measured by negative sexually transmitted infection (STI) tests, showing a positive effect during the period of payment 26. Yet the qualitative study and post-intervention follow-up for this trial suggested a need for ongoing cash payment to sustain protection among female participants.…”
Section: Morally Relevant Considerations For Selecting Conditionalitiesmentioning
confidence: 97%
“…Conditioning on outcomes that are significantly influenced by genetic predisposition and physiology can discriminate against many deserving beneficiaries. The RESPECT trial in Tanzania presents an example where biological and social factors contributed to women's being disproportionately disadvantaged in attaining the conditionality 26. The programme conditioned payments on negative STI tests as a proxy for safe sex.…”
Section: Morally Relevant Considerations For Selecting Conditionalitiesmentioning
confidence: 99%